ETNOMATEMATIKA DALAM PENCIPTAAN WAYANG GUNUNGAN JAWA: ETHNOMATHEMATICS IN THE CREATION OF JAVANESE GUNUNGAN WAYANG - Pandu Pramudita; Ismail Bambang Subianto (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2024)
Wayang gunungan is a figure that is always there and needed in every puppet show. However, the shape and size of wayang gunungan knowledge is still limited by the adaptation. Therefore, this study seeks to explain the basis for measuring wayang gunungan. The theory used to explain the measurement technique of wayang gunungan is ethnomathematics. The method used in this study is qualitative with an experimental approach. This study resulted that wayang gunungan has three size variations, that are small with high of three spawns more than one palm and width of two spawns, medium with high of four spawns and width of two spawns more than one palm, and large with height of five spawns and width of three feet. The results of this research are expected to be used as a reference in the process of creating mountain puppets, especially in determining their size.